Modeling and forecast of gas hydrate distribution in the Black Sea: main principles and approaches - Iemelianov, Volodymyr; Ivanik, Olena; Kukovska, Tamara; Fedoronchuk, Natalia; Shuraiev, Ihor; Petrushenko, Eduard; Hadiatska, Kateryna (Frontiers in Earth Science, 2025)
Gas hydrates are prevalent in marine sediments in regions characterized by certain bathymetry, geomorphology, lithology, and physics (i.e., low temperature and high pressure conditions). The gas hydrates in the Black Sea serve as not only a promising source of energy and chemical resources but also as indicators of active fault zones and sites where the latest geological and geochemical processes are unfolding. The main goal of the present studies is to examine the main factors influencing gas hydrate formation, to understand their combinations and priority, and finally to demonstrate the potential of the integrated technique for gas hydrate abundance at the regional scale. This study employs a structured workflow consisting of database compilation, geological process analysis, identification of key gas hydrate indicators, GIS-based modeling, and hazard assessment. A comprehensive GIS project for the Black Sea was developed to integrate diverse datasets, including geological, geomorphological, and oceanographic information. Spatial analysis and modeling techniques, including weighted overlay methods, were applied to assess the influence of geological and environmental factors on gas hydrate formation. Spatial analyses confirm that gas hydrates are primarily confined to continental slope, where active geological processes such as landslides and methane seepage are present. Key controlling factors include seabed geomorphology, lithology, tectonic structures, and fluid migration pathways. Structural and tectonic analysis revealed a strong correlation between gas hydrate distribution and fault systems. Additionally, mud volcanoes, paleo-river canyons, and fluid migration structures play a crucial role in hydrate formation. A susceptibility map of the Black Sea gas hydrates was created using weighted ranking of geological, geomorphological, and oceanographic parameters. The susceptibility inference process has revealed substantial knowledge gaps, as the uncertainty analysis identifies large seafloor regions with insufficient data or extremely low data density. The developed model could be applied for a better understanding of the vulnerability of areas, and to apply the methods of local predictions of gas hydrates. This model highlights potential hydrate-bearing zones and serves as a predictive tool for future exploration and hazard mitigation. This study also provides valuable insights into marine geohazard preparedness, risk reduction, and sustainable practices in the Black Sea.